2022
DOI: 10.1126/sciadv.abo4173
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin-3 confines AMPA receptors into nanoclusters, thereby controlling synaptic strength at the calyx of Held synapses

Abstract: The subsynaptic organization of postsynaptic neurotransmitter receptors into nanoclusters that are aligned with presynaptic release sites is essential for the high fidelity of synaptic transmission. However, the mechanisms controlling the nanoscale organization of neurotransmitter receptors in vivo remain incompletely understood. Here, we deconstructed the role of neuroligin-3 (Nlgn3), a postsynaptic adhesion molecule linked to autism, in organizing AMPA-type glutamate receptors in the calyx of Held synapse. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 83 publications
3
16
0
Order By: Relevance
“…These differences suggest that a distinct set of signalling cascades underlies postsynaptic reorganisation by Aβ treatment compared with that during LTD. More importantly, Aβ-treated synapses showed a significant reduction in the local enrichment of GluA1 and PSD-95 to RIM nanoclusters compared with the controls. Because adhesion molecules have been shown to mediate transsynaptic nanoalignment, [16,19,21] this reduction in transsynaptic protein enrichment may result from alterations in adhesion molecules by Aβ. [50] Cultured primary neurons incubated with soluble Aβ oligomers have been widely used as an in vitro model to feature AD pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences suggest that a distinct set of signalling cascades underlies postsynaptic reorganisation by Aβ treatment compared with that during LTD. More importantly, Aβ-treated synapses showed a significant reduction in the local enrichment of GluA1 and PSD-95 to RIM nanoclusters compared with the controls. Because adhesion molecules have been shown to mediate transsynaptic nanoalignment, [16,19,21] this reduction in transsynaptic protein enrichment may result from alterations in adhesion molecules by Aβ. [50] Cultured primary neurons incubated with soluble Aβ oligomers have been widely used as an in vitro model to feature AD pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…[17] These nano-architectures are undergoing vigorous reorganisation during synaptic plasticity and development, [17,21] and disruption of these organisations leads to deficient transmission both in vitro [16,19] and in vivo. [21] Despite the significant modulation of synaptic functions by these subsynaptic nano-organisations, it is still unknown how these synaptic nanoarchitectures are reorganised in pathological conditions such as AD.…”
Section: Introductionmentioning
confidence: 99%
“…The functional difference between NLGN2 and NLGN3 indicated that their small structural differences may cause a huge functional gap. Our results showed that the differences in interface area and orientation are the small structural differences between NLGN2 and NLGN3, which possibly confer the ability of NLGN2 to determine inhibitory synaptic transmission in neurons ( 23 ) and confer the ability of NLGN3 to control AMPAR-mediated basal excitatory transmission ( 69 ). Taken together with the previously reported complex structure of NLGN2 and MDGA1 ( 40 ), it is possible that the different orientations of NLGNs may also affect their interactions with MDGAs.…”
Section: Discussionmentioning
confidence: 86%
“…To become functional, assembled ionotropic receptors must be transported to the plasma membrane and clustered at post-synaptic elements, where they are immobilized by synaptic scaffolding proteins. In rodents, several scaffolding proteins have been identified for localizing ionotropic GABA (neuroligin 2, collybistin, gephyrin) [8][9][10], glutamate (PSD95, neuroligin 1 and 3) [11][12][13], and ACh (rapsyn, MuSK) receptors [14,15]. Analysis of invertebrate synapses have identified additional synaptic scaffolds.…”
Section: Introductionmentioning
confidence: 99%